Diffusion of Digital Learning: Increasing Numeration Literacy and Strengthening Pancasila Learners - Sukestiyarno, Sukestiyarno; Kartono, Kartono; Priyanto, Sugeng; Setiawan, Agung; Kusuma, Dani (Jurnal Abdimas, 2023)
Teachers in Semarang City especially those who join in Group Teacher Work (KKG) complained low ability Study independent participant educate. This thing impact on achievement literacy numeracy is also decreasing. Required earnest effort _ For help the participants educate with introduce approach innovative learning. Project devotion public designed with objective For invite teachers to do so become an internal model utilization technology , in particular through use approach learning digital based . Approach This aim For increase literacy numeracy participant educate and strengthen profile Pancasila students . Learning process started with guide about method designing device learning use Learning Management System (LMS). Digital learning This called “e-sigma” with covers complete material _ including explanation detail , summary , test formative , as well key answer with focus on solving problem. Teachers take advantage module This For give tasks Study independent to participant educate . At face face in class , the teacher plays a role as helpful facilitator _ participant educate collaborate , investigate concept , and finally find conclusion draft in a way independent . Purpose of service public This teacher can : 1) design device learning , incl module learning ; 2) carry out learning simulation with use tool help e-sigma; and 3) utilizing module media For increase literacy numeracy and strengthening profile Pancasila students . Training methods carried out Steps 1 ) identify teacher needs in matter learning ; 2) establish standard achievements in training ; 3) give training simulation with e-sigma; 4) evaluate achievement teacher's abilities in training ; and 5) do reflection over the training process that . Data obtained analyzed with use statistics descriptive . The result of devotion public This show that device resulting learning _ from training with the e-sigma LMS is valid, and its implementation in form simulation is effective and impactful potential increase achievement participant educate.